Dydaktyczne cele i założenia badań nad odbiorem liryki w szkole = Didactic Objectives and Assumpted Researches on the Comprehension of Lyrics in School - Uryga, Zenon (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The linear scheme of a communication sequel (transmitter - literary mark - recipient) is not quite sufficient to explain the specific facts of comprehension of literature in school. The interpretation of the literary mark is decided - here, as in every other case - by the scope of community between the transmitter and the recipient in the field of experience. This scope is changeable and depends on the character of interaction in the field of didactic intervention. Researches on comprehension of lyrics in school allow in practice the elimination of observing the transrnitter, but compel to focus on three elements of the communication sequel: a) characteristics of the mark, b) perceptional functions and the recipient's, attitude, c) the field of didactic intervention.
Keywords: dydaktyka literatury; liryka; badania